APLIKASI WATER STIMULATING FEED (WSF) PADA MEDIA KULTUR Navicula sp - Wiwie Soemarjati; Abdul Muqsith (Samakia : Jurnal Ilmu Perikanan, 2014)
Navicula sp is a microalgae that is widely used for activities in the field of fisheries, particularly on Abalone hatchery which is now being developed. Stimulating Feed Water Usage (WSF) is expected to improve the quality and quantity of Navicula sp. The purpose of this study was to obtain information Navicula sp culture techniques with Water Stimulating Feed. This study used six treatments and three replications, namely: treatment A = Fertilizer standards, B = Fertilizer standard 80% and WSF 20%, C = Fertilizer standard 60% and WSF 40%, D = Fertilizer standard 40% and WSF 60%, E = Fertilizer standard 20% and WSF 80% and F = WSF 100%. The results showed that the optimum growth was greatest in treatment C = 99.33 x 104 cells/ml, followed by treatment D = 88 x 104 cells/ml, treatment E = 80.33 x 104 cells/ml, treatment F =78 x 104 cells/ml, treatment B = 59.33 x 104 cells/ml and treatment A =48.66 x 104 cells/ml. Thus the use of the WSF can affect the growth of Navicula sp. The observation of water quality on all treatments are in normal condition and temperature data obtained = 30-31 oC, salinity = 35 ppt, DO = 4.7 to 5 ppm, pH = 8.28 to 8.41 and NO2 = ,0.001 to 0.024 ppm